A life‐table analysis of the intrauterine fate of malformed human embryos and fetuses. Issue 8 (4th March 2021) - Shiota, Kohei
Abstract: Background: Various malformations are frequently encountered in spontaneously aborted embryos and fetuses. Thus, spontaneous abortion appears to be a screening device for abnormal conceptuses ("teratothanasia"). However, the prevalence rate of abnormal conceptuses at each gestational stage is unknown and the true picture of prenatal natural selection remains to be elucidated. Methods: An in utero life‐table of normal and malformed human conceptuses was constructed utilizing the data for human embryos and fetuses procured after therapeutic abortion and kept in the Kyoto Collection of Human Embryos ( N = 21, 798). Results: The prevalence of external major malformations was estimated to be 9.6% at the start of the fifth week after fertilization and drop to 9.2, 8.5, and 7.5% during the following weeks. The malformation rate decreased to 5.3% by the end of the embryonic period (the eighth week), 2.8% by the 13th week and 1% at term. The prenatal mortality rate of externally malformed conceptuses between the fifth week of gestation and term was 92.8%, whereas the corresponding rate for externally normal embryos was 24.9%. The prenatal mortality rates of embryos with neural tube defects and holoprosencephaly were 96.0 and 99.7%, respectively. Conclusions: Abnormal development occurs frequently early in development and many of the malformed embryos/fetuses die in utero to end in spontaneous abortion. Natural prenatal screening of abnormal conceptuses most likely contributes to reducing the birth of malformed infants.